(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper critically examines the relationship between technological modernity and the gradual erosion of Indigenous Knowledge Systems (IKS), with specific reference to the Indian context. It argues that contemporary digital infrastructures—while offering unprecedented global connectivity and operational efficiency—simultaneously accelerate epistemic homogenization, digital colonialism, and cultural Westernization. Drawing on decolonial theory, Science and Technology Studies (STS), and recent scholarship on data sovereignty, the study situates the marginalization of IKS within a broader socio-technical framework. Employing a critical-interpretive methodology that triangulates documentary policy analysis with three India-specific case studies—the National Education Policy (NEP) 2020 and the EdTech sector, generative artificial intelligence (AI) and linguistic marginalization, and Adivasi agricultural-data extraction—the paper demonstrates how digital systems restructure cognition, commodify cultural memory, and displace indigenous epistemologies. The analysis identifies four structural mechanisms of erosion—epistemic standardization, algorithmic bias, data dispossession, and cognitive restructuring—which together produce a condition of epistemic dependency in which interpretive authority shifts from communities to privately owned platforms. Empirical indicators are integrated throughout: India recorded 19,569 raw mother-tongue returns in the 2011 Census yet officially recognizes only 121 languages, while English constitutes roughly 46% of the most recent Common Crawl corpus and over 90% of the training data underpinning large language models. The paper advances two conceptual models—a comparative epistemological paradigm and an epistemic erosion–revitalization framework—and argues for a paradigm of technological sovereignty that critically engages digital advancement while safeguarding pluralistic knowledge ecosystems. The findings carry implications for education policy, AI governance, and indigenous data rights, suggesting that hybrid pedagogies, collective-consent data protocols, and decolonial AI design can convert digital infrastructure from a vector of erosion into an instrument of epistemic revitalization.